2018
DOI: 10.1111/1556-4029.13985
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregating Mass Public Shootings: A Comparative Analysis of Disgruntled Employee, School, Ideologically motivated, and Rampage Shooters

Abstract: This study compares the demographic, background, motivation, and pre‐event and event‐level behaviors across four types of mass public shooters: disgruntled employee, school, ideologically motivated, and rampage offenders. Using a database containing detailed information on 318 mass public shootings that occurred in the United States between 1966 and 2017, we find systematic differences in the characteristics, motivations, target selection, planning, and incident‐level behaviors among these offenders. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 28 publications
1
49
0
1
Order By: Relevance
“…In other words, incel homicide offenders, seeking ultimate power and revenge, simply bypass rape, committing sexualized mass murder instead (also see Murray, 2017). Although mass murder motivated by incel ideology seems to be its own unique type of crime, it is consistent with the pseudocommando style mass murderer (Knoll, 2010), while also reflecting some, though not all, elements of ideologically motivated mass public shootings (Capellan, et al, 2019). Incels feeling extreme helplessness and hopelessness in multiple areas of life functioning crave ultimate power and revenge via mass murder, not rape.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In other words, incel homicide offenders, seeking ultimate power and revenge, simply bypass rape, committing sexualized mass murder instead (also see Murray, 2017). Although mass murder motivated by incel ideology seems to be its own unique type of crime, it is consistent with the pseudocommando style mass murderer (Knoll, 2010), while also reflecting some, though not all, elements of ideologically motivated mass public shootings (Capellan, et al, 2019). Incels feeling extreme helplessness and hopelessness in multiple areas of life functioning crave ultimate power and revenge via mass murder, not rape.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study examining characteristics of mass public shootings, which is applicable to six of the seven offenders in this sample (albeit one of the six used a vehicle as the sole weapon in his public massacre), identified specific features of different types of mass public shooting offenders-disgruntled employees, school shooters, ideologically motivated, and rampage shooters (do not fit one of the other types) (Capellan, Johnson, Porter, & Martin, 2019). While incel mass murderers are motived by a unique ideology rooted in sex-negativity, which is different than other ideological motivated mass shooters (i.e., political and religious-based), several offenders in the current sample experienced such severe employment problems that perhaps it is a little surprising that they did not seriously consider bifurcation at a workplace setting as part of their attacks.…”
Section: Employment Issuesmentioning
confidence: 99%
“…In addition, Capellan, Johnson, Porter, and Martin () found that a larger proportion of active and mass shooters since 2010 have been ideologically driven than during any prior decade since the 1960s, so a significant proportion of these perpetrators may have been seeking attention for their cause (and/or themselves). In fact, committing a public mass shooting may have become significantly more attractive to ideological extremists than attacking with other weapons because the likelihood of “success” is so much higher.…”
Section: Increased Desires For Fame Attention or Infamy Among Publimentioning
confidence: 99%
“…Des Weiteren gibt es Vergleiche von Amokläufern in den USA und Selbstmordattentätern im Nahen Osten (Lankford & Hakim, 2011) sowie terroristischen Einzeltätern/Amokläufern und nichtideologischen Mördern (Liem, van Buuren, de Roy van Zuijdewijn, Schönberger & Bakker, 2018). Eine Studie verglich Amokläufer an Schulen und ideologisch motivierte Attentäter in den USA in Bezug auf demographische Charakteristika, Motivation und Verhalten vor und während der Tat (Capellan, Johnson, Porter & Martin, 2018). Sie zeigte, dass Amokläufer und Attentäter meist männlich sind.…”
Section: Tat-und Tätermerkmale Von Terroranschlägen Und Von Amokläufen Im Bildungskontextunclassified